A relação do perfil vertical do vapor d água com a convecção profunda na Amazônia - Rocha, Antônio Alciélio Amorim da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
This work represents an exploratory study of the relationship between the vertical distribution of water vapor and deep atmospheric convection in the Amazon region. A climatology of the water vapor profile is developed for a ten-year period of record to examine variation between wet, dry and the transitional seasons. In addition, a climatology is developed to analyze the activation and suppression of deep convection with respect to the vertical profile of water vapor. Data utilized to develop this climatology include, radiosondes, water vapor retrievals using GPS radio-occultation techniques and water vapor retrievals from the AQUA satellite. Results show that water vapor homogeneity over the Amazon region extends to almost 400 km. The seasonal controls on convective rainfall (i.e., wet versus dry season) are strongly modulated by humidity variability in the 850 to 500mb layer. Convective events, however, are strongly modulated by the total water vapor found in the 850 to 700mb level. Comparison with thermodynamic instability argues for the dominance of total water vapor content in determining when deep convection occurs, not instability.
Keywords: Amazônia